Attitudes towards Fake News from the Perspective of the Experience of Adult Poles - Michał Szyszka; Arkadiusz Wąsiński; Artur Fabiś; Paweł Buchwald (Communication Today, 2025)
Falsification and manipulation of information, using it for image, material or political gain, is a significant phenomenon of contemporary social communication, and no doubt, its scale and significance have made fake news the subject of numerous studies. The purpose of this article is to analyse the attitudes of adult Poles toward fake news, based on the results of a qualitative study conducted as part of the national Infostrateg programme. The study was designed to identify respondents’ knowledge and attitudes about fake news, their awareness of the dangers of information manipulation and how they deal with disinformation. A semi-structured individual interview method was used, which made it possible to capture subtle aspects of the respondents’ experiences. Data analysis was carried out according to a semi-inductive model, using open coding and comparative analysis. Sampling was based on the criterion of maximum variation, which made it possible to capture a variety of perspectives on fake news. The results indicate that fake news is perceived as an integral part of the modern infosphere, and its presence is widely accepted, although it evokes distrust and caution. Respondents consider them a tool of social disintegration, manipulation of worldviews and network marketing. They show negative emotions toward the phenomenon, while declaring high resistance to information manipulation. The meaning attributed to fake news is reduced to four coherent categories: FN as the creation of a falsified image of reality; as a tool of social disintegration; as a tool for changing or strengthening worldviews; and as a tool of network marketing.